Persepsi Jurnalis di Bali Terhadap Nilai Berita Jurnalisme Warga (Citizen Journalism) - Fayani, Adinda; Amanda Gelgel, Ni Made Ras; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2019)
ABSTRACT This study aimed at determining the perception of journalists in Bali on the news value of citizen journalism seen from the performance of citizen journalism in disseminating information or news. This research used descriptive quantitative method. The sampling technique used was purposive sampling. The results showed that the average perception of journalists in Bali on the news value of citizen journalism with the overall score of the indicator of news value in terms of providing news or information was 3.58. The average meaning was a good or positive category. It meant that citizen journalism was considered a phenomenon as well as a forum for people's aspirations. Citizen Journalism was considered capable of playing a role in helping mainstream media journalists in spreading any information or news.   Keywords : Citizen Journalism, News Value, Perception.